2003
DOI: 10.1149/1.1605422
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Evaluation of Hydrodynamic and Brush Contact Effects on Particle Removal during Brush Scrubbing

Abstract: Wafer cleaning following chemical mechanical planarization, especially brush scrubbing, is a critical step in semiconductor device manufacturing that is not adequately understood. In this work, the effects of hydrodynamic forces, brush-particle adhesion, and brush-particle momentum transfer are quantified for spheroidal particles having aspect ratios ranging from 0.2 to 5. A critical particle Reynolds number approach was used to determine the effect of the hydrodynamic force and brush-particle adhesion on part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Most of the research corroborates the typical behaviour of brushing processes: higher rotational speeds of the brush (Moumen and Busnaina, 2001;Moden et al, 1989;Zhang et al, 1998), pressures or penetrations (Moumen andBusnaina, 2001;Moden et al, 1989;Burdick et al, 2003), and cleaning times (Moumen and Busnaina, 2001;Zhang et al, 1998) improve cleaning effectiveness.…”
Section: Related Worksupporting
confidence: 66%
See 1 more Smart Citation
“…Most of the research corroborates the typical behaviour of brushing processes: higher rotational speeds of the brush (Moumen and Busnaina, 2001;Moden et al, 1989;Zhang et al, 1998), pressures or penetrations (Moumen andBusnaina, 2001;Moden et al, 1989;Burdick et al, 2003), and cleaning times (Moumen and Busnaina, 2001;Zhang et al, 1998) improve cleaning effectiveness.…”
Section: Related Worksupporting
confidence: 66%
“…10). Lastly, it is suggested that larger pressures or penetrations improve cleaning efficiency (Moumen and Busnaina, 2001;Moden et al, 1989;Burdick et al, 2003). Loosely speaking, in the case of street sweeping a very small penetration may produce insufficient brush-surface contact and a low effectiveness (as, for example, in Fig.…”
Section: Summary and Additional Remarksmentioning
confidence: 99%
“…[8][9][10] Pencil type brushes are used for traversing, 11,12 and in some cases have added rotation. 13 Recently, semiconductor devices have developed significantly. In addition to scaling down, many such devices have three-dimensional structures, making CMP processes significant.…”
mentioning
confidence: 99%
“…The adhesion model used here to describe interactions between particles or cantilevers and photomask substrates is summarized by equations (1)- (5). Based on the random phase angle in the Fourier transform algorithm, a distribution of adhesion forces results for each system of interest.…”
Section: Theorymentioning
confidence: 99%
“…Contaminant particles as small as 3-10 nm will soon be of significant concern during manufacturing. While nanoparticles adhere to surfaces weakly compared to micrometer-size particles, they are often more difficult to remove because most cleaning protocols apply a removal force on the particle in a fluid environment in which a boundary layer is present [1][2][3][4][5][6][7]. These boundary layers may be up to 2-3 orders of magnitude larger than the largest contaminant particle of interest.…”
Section: Introductionmentioning
confidence: 99%